The Effect of Think Aloud on Performance and Brain Oxygenation During Cycling – An Exploratory Study. Issue 4 (August 2022) - Whitehead, Amy; Montgomery, Catharine; Swettenham, Laura; Robinson, Nicola J.
In this study, we aimed to investigate the effect of Think Aloud (TA) on performance in trained and untrained participants, using functional Near Infrared Spectroscopy, during incrementally paced cycling. A mixed design was implemented with cycling expertise (10 untrained vs. 9 trained) as the between groups variable and trial stage (5 stages of increasing effort), and condition (silent vs. TA) as within groups independent variables (IVs). Dependent measures were changes in cortical oxygenation (O2 Hb) in 12 areas of the prefrontal cortex (PFC) and physiological indicators of percentage heart rate maximum (%HRmax), average power output (APO), peak power output (PPO), rate of perceived exertion (RPE) and blood lactate ([La]b) over time. Trained cyclists had higher APO and significantly higher PPO from stages 2–5, in addition to a greater increase in PPO over the duration of the test (range 168W–480 W vs. 133W–313 W). There were significant main effects of stage on %HRmax, Bla and RPE ( p < .001), with effect sizes (ήp 2 ) ranging from .31 to .97. On average, HRmax%, [La]b and RPE were significantly lower after stage 2 onwards within the TA trial than the silent trial, even though similar power outputs were obtained. Thus, the TA trial elicited a better pacing strategy. There was no main effect of group on changes in O2 Hb, though O2 Hb did change as a function of stage in four areas of the PFC, and as a function of condition in one area. In this first study to assess the effects of TA on performance during self-paced cycling, TA did not disrupt performance outcomes at low through to high levels of physical exertion for either untrained or trained participants.